Effects of motor-cognitive interaction based on dual-task gait analysis recognition in middle age to aging people with normal cognition and mild cognitive impairment - Zheng, Yuxin; Lang, Shijuan; Liang, Junjie; Jiang, Yongchun; Zhao, Biyi; Chen, Hongxin; Huang, Dongqing; Li, Qinyi; Liu, Huijin; Chen, Shudi; Yilifate, Anniwaer; Xu, Fangqiu; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Mild cognitive impairment (MCI) is considered as a transitional stage between cognitive normality and dementia in the elderly, and the risk of progression to Alzheimer’s disease is 10 to 15 times higher than that in the normal population. However, there is still a lack of objective evaluation methods for the early diagnosis of MCI. Methods: In this study, 68 subjects who met the inclusion criteria were divided into the MCI group (30 subjects) and the normal elder (NE) group (38 subjects). Clinical function assessments (cognitive function assessment, walking function assessment, and daily living activities assessment) and dual-task three-dimensional gait analysis (walking motor task and walking calculate task) were performed in both groups. The obtained spatial-temporal parameters and joint angle parameters were dimensionally reduced by factor analysis to screen out the key biomechanical indexes, and then Dual-task Cost (DTC) was calculated to perform intra-group comparison (task factors) and inter-group comparison (group factors). Results: The factor analysis results of this study showed that the cadence parameter had the highest weight in all three walking tasks. Moreover, the MCI group showed significant differences in cadence both in the walking motor task (WMT) versus walking task (WT) and walking calculate task (WCT) versus WT， whereas NE groups just showed a significant difference in cadence in WMT versus WT. The differences between the MCI group and NE group were just shown for DTCcadence in WCT, whereas no differences were found for cadence in any of the three walking tasks. Conclusions: In this study, the dual-task three-dimensional gait analysis and factor analysis were used to target the key spatial-temporal parameters and articular angle biomechanical parameters for early diagnosis of MCI, to improve clinical diagnostic effectiveness. Our results indicate that DTC cadence based on cognitive-motor dual-task (WCT) gait analysis has potential application in early MCI recognition, and the weight of joint Angle on MCI recognition needs further research.